2020
DOI: 10.1097/nnr.0000000000000413
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of the Human Papillomavirus by Social Stratification Factors

Abstract: Background Social determinants of health explain most health inequities. Intermediate determinants dictate differences in the exposure and vulnerability of people based on social stratification. Vulnerable women (lower education level, older age, uninsured, etc.) have lower adherence to recommended Pap smear screening guidelines. However, a gap remains concerning the effect of social determinants on human papillomavirus (HPV) infection. Objectives The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
1
8
1
5
Order By: Relevance
“…Students majored in medical specialty and (or) had a better academic performance did well in all questions above, similar to previous literatures [ 35 , 36 ]. Different from a previous study [ 37 ], there was no difference in any question above among students in different residential areas, which might be because of the popularization of the Internet and the narrowed gap of our respondents in awareness and knowledge of HPV infection. We observed that parents’ education level had difference in some of questions above, which indicated that the improvement of the parents’ education level might take effect in increasing the knowledge among them [ 38 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Students majored in medical specialty and (or) had a better academic performance did well in all questions above, similar to previous literatures [ 35 , 36 ]. Different from a previous study [ 37 ], there was no difference in any question above among students in different residential areas, which might be because of the popularization of the Internet and the narrowed gap of our respondents in awareness and knowledge of HPV infection. We observed that parents’ education level had difference in some of questions above, which indicated that the improvement of the parents’ education level might take effect in increasing the knowledge among them [ 38 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The respondents with family history of CC were more potential to heard about CC and HPV. Additionally, the characteristics of personal education level, family history of other cancers and having received HPV vaccine suggested much difference in questions above, similar to previous surveys [ 21 , 37 ]. The results of the three multivariable logistic regression models showed that age, grade and major were three independently significant predictors.…”
Section: Discussionsupporting
confidence: 78%
“…At the individual level, several factors have been analyzed and reported as associated with low HPV vaccination coverage, especially low schooling, low income, living in a rural area, low access to information and health services, and barriers imposed by religious dogmas [10][11][12][13][14] . Meanwhile, population analyses, with aggregated data, contribute to understanding social or structural determinants connected to the vaccination coverage achieved in a geographic area.…”
Section: Rev Bras Epidemiol 2021; 24: E210001mentioning
confidence: 99%
“…In the 1st year of vaccination (2014), 87% of the Brazilian municipalities had achieved the goal target of 80% coverage for the first dose among eligible girls; this number dropped to 32% of the cities for the second dose ( 18 ). Numerous individual factors have been described as associated with low HPV vaccine coverage, including low educational level, low income, countryside residence and low access to information and health services ( 19 22 ). At a population level, social/structural determinants are paramount, such as living conditions, presence of sewage, piped water, garbage collection, etc.…”
Section: Cervical Cancer Mitigation Through Vaccination Screening And...mentioning
confidence: 99%